An active thermal management strategy for switched reluctance drive system with minimizing current sampling delay. (November 2020) - Yang, Qingqing; Ma, Mingyao; Yang, Shuying; Zhang, Xing
Abstract: The reliability of switched reluctance drive system (SRD) can be improved by an effective thermal management strategy, when SRD is exposed to harsh environment and anything could happen throughout the life time. In order to avoid overtemperature fault of power converter, there are generally two methods: derating and switching frequency reduction. However, the derating methods will lead to insufficient power and even affect the safety of SRD. An active thermal management strategy for SRD with minimizing current sampling delay is proposed in this paper, which can ensure that the temperature of power converter will not exceed the maximum allowable temperature under any working condition by adjusting switching frequency. In the proposed strategy, the sampling method can ensure that the output performance of SRD at lower switching frequency is good as that of traditional sampling method at normal switching frequency by optimizing the sampling point.